Rational Antibiotic Use in Outpatient Care: Strategies to Combat Antimicrobial Resistance (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The irrational use of antibiotics in outpatient settings significantly contributes to the emergence and spread of antimicrobial resistance (AMR), posing a major global public health threat. This review article evaluates current patterns of antibiotic prescription in outpatient care, identifies key drivers of inappropriate use, and discusses evidence-based strategies to promote rational antibiotic use. Emphasis is placed on antimicrobial stewardship programs, prescriber education, patient awareness, diagnostic support, and policy interventions. Integrating these approaches is critical to curbing AMR, preserving antibiotic efficacy, and ensuring optimal patient outcomes in community healthcare. The rise of antimicrobial resistance (AMR) is a critical global health threat that undermines the efficacy of antibiotics and poses serious risks to public health. Outpatient settings account for a significant portion of antibiotic prescriptions, many of which are unnecessary or inappropriate. This has contributed substantially to the emergence and spread of resistant microorganisms. Rational antibiotic use in outpatient care is thus essential for preserving antibiotic effectiveness and safeguarding future treatment options. This article explores current challenges in outpatient antibiotic prescribing, evaluates evidence-based strategies to improve prescribing practices, and emphasizes the importance of stewardship interventions, education, and surveillance. By integrating clinical guidelines, diagnostic tools, and patient engagement, healthcare systems can promote responsible antibiotic use and combat AMR effectively.